(untitled) (Global Journal of Science Frontier Research, 2018)
Physidae is the most world widely dispersed and commonly encountered family of freshwater pulmonates. Physa acuta Draparnaud, 1805, one of its common, occurring species belongs to Family Physidae of Class Gastropoda. It is a globally invasive freshwater gastropod species that had been recorded from only some states (10) of India till date. The present study reports the occurrence of this family along with the species for the first time from the freshwater bodies of U.T. Chandigarh. The species identification has been made by external morphology and anatomical characteristics like penial complex. The family has shown its dominance in still waters and slow-moving water bodies, rich in organic matter while the species has been found in other freshwater aquatic ecosystems too, though in very less percentage.